TRANSMUTATION OF NUCLEAR WASTE (PLUTONIUM AND MINOR ACTINIDE) USING ACCELERATOR DRIVEN SUBCRITICAL SYSTEM WITH FUEL CONSISTS OF UO2(NO3)2, PUMA(NO3)4 AND HNO3 - SRY NOVITA (NIM : 10214025), JESY
Nuclear waste must have a processing mechanism so as not to endanger environmental conditions. There are several methods of processing nuclear waste including geological Repositories of nuclear waste or reprocessing of the waste to be used as fuel again. In this study nuclear waste is processed by transmutting, using an Accelerator Driven Subcritical System (ADS). ADS is a system consisting of a subcritical reactor core and a particle accelerator. Accelerated particles will pound the heavy nucleus, the reaction between the particles and the heavy nucleus is called a spallation reaction which produces spallation products. Nuclear waste which was processed in this study is Plutonium and Minor Actinide. The fuel used is Uranyl Nitrate which is added with Plutonium and Minor Actinide (UO2(NO3)2, PuMA(NO3)4 dan HNO3). Fuel density depends on the concentration of this three solutions. In this study, concentration of the fuels solution were performed to make the reactor reach the subcritical conditions in RGPuMA, WGPuMA and SGPuMA. Then also will be seen the changes of plutonium and minor actinide density in RGPuMA, WGPuMA and SGPuMA at 100 MWth and 200 MWth.